Temperature analysis of hadronic current simulations using relativistic hydrodynamics for heavy-ion collisions scenarios - Chaires Arciniega, Darío (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
This thesis investigates the application of relativistic ideal hydrodynamics to simulate the early-stage evolution of Quark-Gluon Plasma (QGP) in heavy-ion collisions (HIC). The study aims to test the feasibility of using an ideal fluid approximation—neglecting viscosity and employing a simple equation of state (EoS) to describe the thermodynamic and hydrodynamic properties of QGP, a deconfined state of matter theorized to mimic conditions of the early universe. The work leverages the CAFE code, a relativistic hydrodynamic solver, adapted to HIC scenarios by implementing Monte Carlo Glauber initial conditions and interpolating energy density profiles from the ECHOQGP framework.

Esta tesis investiga la aplicación de la hidrodinámica ideal relativista para simular la evolución temprana del plasma de quarks-gluones (QGP) en colisiones de iones pesados. El estudio busca evaluar la viabilidad de usar una aproximación de fluido ideal despreciando la viscosidad y empleando una ecuación de estado simple para describir las propiedades termodinámicas e hidrodinámicas del QGP, un estado desconfinado de la materia que se teoriza para imitar las condiciones del universo primitivo. El trabajo utiliza el código CAFE, un solucionador hidrodinámico relativista, adaptado a escenarios de colisiones de iones pesados mediante la implementación de las condiciones iniciales de Monte Carlo Glauber y la interpolación de perfiles de densidad de energía del marco ECHO-QGP.
Facultad de Ciencias Físico Matemáticas. Maestría en Ciencias en Ingeniería Física
Keywords: info:eu-repo/classification/cti/1; FISMAT-M-2025-1508; Plasma de quarks y gluones; Método de volumen finito; Variables; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19463